Effective Contrast Enhancement techniques for Fundus images - et. al., Zareena Hassanbee M S A, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Diabetic Retinopathy is a medical condition associated with the eye suffered by a major population of diabetic patients. The progression of this micro-vascular condition of the eye is mainly targeted on small blood vessels of the retinal area. A major characteristic of this condition is the presence of exudates which is actually a fluid that may ooze out from affected regions, may it be a cut or any infected region. The situation when left untreated yields to blindness which is why early detection is the best take. Using image processing we can simplify the data analysis of the exudates images and ease the diagnosis in an efficient way. The fundus image we obtain for diagnosis will be in RGB model format. In order to distinguish the exudates, blood vessels, hemorrhage, optic disk and other features, it is essential to enhance the colour of the image. In this paper we will discuss the existing techniques that are present for this contrast adjustment and propose the most efficient method for the same. Following this, we will also look into the segmentation process which is used for OD and exudate extraction.